Association between telehealth use and general practitioner characteristics during COVID-19: findings from a nationally representative survey of Australian doctors - Anthony Scott; Tianshu Bai; Yuting Zhang (BMJ Open)
Objective To investigate factors associated with the use of telehealth by general practitioners (GPs) during COVID-19.Design A nationally representative longitudinal survey study of Australian doctors analysed using regression analysis.Setting General practice in Australia during the COVID-19 pandemic.Participants 448 GPs who completed both the 11th wave (2018–2019) of the Medicine in Australia: Balancing Employment and Life (MABEL) Survey and the MABEL COVID-19 Special Online Survey (May 2020).Outcome measures Proportion of all consultations delivered via telephone (audio) or video (audiovisual); proportion of telehealth consultations delivered via video.Results 46.1% of GP services were provided using telehealth in early May 2020, with 6.4% of all telehealth consultations delivered via video. Higher proportions of telehealth consultations were observed in GPs in larger practices compared with solo GPs: between +0.21 (95% CI +0.07 to +0.35) and +0.28 (95% CI +0.13 to +0.44). Greater proportions of telehealth consultations were delivered through video for GPs with appropriate infrastructure and for GPs with more complex patients: +0.10 (95% CI +0.04 to +0.16) and +0.04 (95% CI +0.00 to +0.08), respectively. Lower proportions of telehealth consultations were delivered via video for GPs over 55 years old compared with GPs under 35 years old: between −0.08 (95% CI −0.02 to −0.15) and −0.15 (95% CI −0.07 to −0.22), and for GPs in postcodes with a higher proportion of patients over 65 years old: −0.005 (95% CI −0.001 to -0.008) for each percentage point increase in the population over 65 years old.Conclusions GP characteristics are strongly associated with patterns of telehealth use in clinical work. Infrastructure support and relative pricing of different consultation modes may be useful policy instruments to encourage GPs to deliver care by the most appropriate method.